Additive manufacturing of microneedles for sensing and drug delivery - GÜNDÜZ, OĞUZHAN (My University, 2024)
Introduction: Microneedles (MNs) are miniaturized, painless, and minimally invasive platforms that have attracted significant attention over recent decades across multiple fields, such as drug delivery, disease monitoring, disease diagnosis, and cosmetics. Several manufacturing methods have been employed to create MNs; however, these approaches come with drawbacks related to complicated, costly, and time-consuming fabrication processes. In this context, employing additive manufacturing (AM) technology for MN fabrication allows for the quick production of intricate MN prototypes with exceptional precision, providing the flexibility to customize MNs according to the desired shape and dimensions. Furthermore, AM demonstrates significant promise in the fabrication of sophisticated transdermal drug delivery systems and medical devices through the integration of MNs with various technologies. Areas covered: This review offers an extensive overview of various AM technologies with great potential for the fabrication of MNs. Different types of MNs and the materials utilized in their fabrication are also discussed. Recent applications of 3D-printed MNs in the fields of transdermal drug delivery and biosensing are highlighted. Expert opinion: This review also mentions the critical obstacles, including drug loading, biocompatibility, and regulatory requirements, which must be resolved to enable the mass-scale adoption of AM methods for MN production, and future trends.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TROPİKAL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; TROPICAL MEDICINE; Farmasötik bilim; Yaşam Bilimleri; Pharmaceutical Science; Life Sciences; 3D printing; additive manufacturing; biosensing; microneedles; transdermal drug delivery